ANALYSIS OF DIGITAL BUSINESS COMMUNICATION STRATEGIES IN INCREASING SALES THROUGH SHOPEEFOOD (A STUDY OF JUICE VENDORS IN SUKARAME, BANDAR LAMPUNG) - Intan Suri Mahardika Pertiwi; Maela Elga Fadilah (Institut Bakti Nusantara, 2026)
This study aims to analyze digital business communication strategies in increasing sales through ShopeeFood among juice vendors in Sukarame, Bandar Lampung. The rapid development of digital platforms has encouraged Micro, Small, and Medium Enterprises (MSMEs) to utilize online media as a means of business communication and product marketing. This research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The research informants consisted of juice vendors and consumers who used ShopeeFood services. The findings reveal that the digital business communication strategies implemented by the vendors include the use of attractive product visuals, digital promotional activities such as discounts and free delivery offers, responsive customer service, and active interaction through application features. These strategies have proven effective in increasing consumers’ purchase intentions and boosting sales performance. Furthermore, the utilization of ShopeeFood enables business owners to expand their market reach and strengthen customer loyalty. However, the study also identified several challenges faced by the vendors, including intense price competition, dependence on platform-based promotional programs, and limited digital technology capabilities. The study concludes that digital business communication strategies implemented through ShopeeFood play a significant role in enhancing the sales performance of culinary MSMEs in the digital economy era. Effective communication, supported by digital platforms, can serve as a strategic tool for improving business competitiveness and sustaining long-term growth.